CAN REUSABLE PACKAGING BE THE FUTURE OF FMCG SUSTAINABILITY? A CASE STUDY ON REGULATORY COMPLIANCE AND CIRCULAR ECONOMY IN INDONESIA - Bintang Ekananda; Anif Farida; Faridz Abdul Chalid Macap (Journal of Innovation Research and Knowledge, 2025)
Single-use packaging significantly contributes to environmental degradation, with plastic pollution becoming a critical issue. While recycling has limitations, reusable packaging offers a viable alternative, particularly for Fast-Moving Consumer Goods (FMCG). This study examines the implementation of a reusable packaging system for chocolate malt powder, developed collaboratively by an FMCG brand and Alner, a reuse operator in Indonesia. Using a qualitative case study approach, it explores the design, regulatory compliance, and operational framework. The results show that reusable systems, compliant with BPOM Regulation No. 23 of 2023 and adhering to Good Manufacturing Practices (GMP), are scalable and legally viable. This research highlights the distinction between reusable packaging and refill models, emphasizing reusable systems as a sustainable, practical solution for FMCG brands to adopt circular economy principles and reduce plastic waste